Enhanced immune response of a bicistronic DNA vaccine expressing fusion antigen Hsp65-Esat-6 of Mycobacterium Tuberculosis with GM-CSF as a molecular adjuvant - Dong,Yan (2013)
This study aimed to construct a bicistronic DNA vaccine expressing fusion antigen Hsp65-Esat-6 of Mycobacterium tuberculosis with cytokine GM-CSF as a molecular adjuvant (pIRES-Hsp65-ESAT-6-GM-CSF, pIRHEG), and the immune response in mice. C57BL/6 mice were immunized with the recombinant plasmid to detect the titer of antibodies, lymphocyte proliferation, the ratio of CD4+, CD8+T cell and IFN ~ γï¼IL-2 secretion. The titer of antibody, lymphocyte proliferation, the ratio of CD4+T and CD8+T cells and IFN ~ γ, IL-2 secretion of pIRHEG group was significant higher than other recombinant plasmid groups, which significant differed by statistical mean. The bicistronic DNA vaccine could induce an effective immune response in mice and could be used as vital ingredient of a new tuberculosis vaccine candidate.